Enhancing strength and toughness of 2-GPa-grade press-hardened steel by novel electroshock treatment - Ye Li; Yanli Song; Jue Lu; Junhao Hu; Yanfeng Gu; Yikuan Yang; Lin Hua (Materials & Design)
This study combined electroshock treatment (EST) with conventional hot stamping to address the poor toughness and strength–toughness trade-off in 2-GPa-grade press-hardened steels. Multiscale microstructural characterization and mechanical testing systematically revealed the intrinsic relationship between microstructural evolution and strengthening–toughening mechanisms. Compared to conventional hot stamping, EST enhanced tensile strength to 2023 MPa (an increase of 5.31 %) and impact energy to 21.5 J (an increase of 22.99 %), achieving a strength–toughness synergy. Microstructural mechanism analysis indicated that the strength enhancement was primarily attributable to the nanoscale ε-carbide precipitation (diameter < 3.6 nm), contributing 327 MPa to yield strength via shear strengthening. The toughness enhancement was linked to dislocation migration and rearrangement in high-energy interfacial regions, including martensitic lath boundaries and (Nb, Ti)C precipitate interfaces, which alleviate stress concentrations. With increasing energy density, the tensile strength decreased slightly to 1841 MPa while the impact energy increased significantly by 43.67 % (25.0 J), with concurrent enhancement in precipitation strengthening (447 MPa). However, the dislocation density drops significantly to 2.28 × 1015 m−2 (a decrease of 63.40 %), weakening dislocation strengthening (648 MPa) and slightly reducing overall strength. Multiple mechanisms, including increased high-angle grain boundaries, accelerated dislocation annihilation at interfaces, and expanded low-strain regions, synergistically alleviated stress concentrations and significantly enhanced toughness.